Epidemiología de las pymes, sector de artes gráficas, acogidas bajo la ley 550 (2014)
Family graphic arts companies, examples of initiators companies, after the stage of growth they had to qualify for the 550 law or bankruptcy law, experience of industry, This situation motivated to carry out a ¨epidemiologico¨ analysis; assimilating to public health situations. We identified 12 companies that accepted that law, then analyzed each of the records in the files of the Superintendency of Industry and Commerce of Colombia, these practices were compared with Japanese management system.